Desinfeksi Novel Corona Virus di Dalam Air Minum PDAM dan Air Limbah Untuk Fase Normal Baru - Gede H. Cahyana (Fakultas Teknik, 2020)
The purpose of this literature review is to review the effectiveness of chlorination in eradicating viruses (and bacteria) in drinking water and wastewater so that people can get scientific information on the practice of eradicating the new Corona virus. The research method was carried out by reviewing scientific articles obtained from the search engine scholar.google.com, the National Library website and textbooks. Chlorine is able to deactivate the virus on objects that are splashed by the patient's saliva. Giving chlorine doses of 0.2–40 mg / l and remaining free chlorine 0.2–0.5 mg / l, chlorination is effective in eradicating viruses and bacteria in drinking water. When the bacteria die, the virus dies or is inactive. The new Corona virus blanket can also be destroyed by chlorine. Researchers have also found genetic traces of the new Corona virus in wastewater. The genetic traces of the new Corona virus found in wastewater could be a latent danger for a new outbreak in the post-pandemic or new normal period. PDAM water that contains chlorine becomes important during the new normal period so it must be provided in public and social facilities.